Methane formation from successive hydrogenation of C over stepped Ni and Ni3Fe surfaces: Effect of surface composition. (12th January 2017) - Yang, Kuiwei; Zhang, Minhua; Yu, Yingzhe
Abstract: As an integral part in methanation, CH4 formation from successive hydrogenation of atomic C was systematically studied over stepped Ni(211) and Ni3 Fe(211) surfaces via periodic density functional theory calculations. The effect of surface composition was explicitly examined by taking into account of two termination structures of Ni3 Fe(211) (the surfaces with NiNi- and NiFe-type step are denoted as Ni3 Fe(211)-AA and Ni3 Fe(211)-AB, respectively). Both alloyed surfaces are found to benefit the initial C hydrogenation through enhancing H adsorption as well as weakening the binding strength of C. Because CH2 generation and subsequent CH2 hydrogenation favor different sites over such stepped surfaces, the step of CH2 migration was proposed and incorporated into the mechanism. The hydrogenation reactions manifest significant structural sensitivity since Ni3 Fe(211)-AB is superior to Ni3 Fe(211)-AA in lowering the overall potential energy surfaces towards CH4 formation. In combination with our previous work focusing on CO activation and dissociation, the present results confirmed the improved activity of Ni3 Fe alloy catalyst for CO methanation suggested experimentally and the Ni3 Fe(211)-AB termination is further identified to dominate the promoting effect. A newly proposed Brønsted–Evans–Polanyi relationship is also found to hold for the successive hydrogenation steps herein. Highlights: CH4 formation on stepped surfaces of Ni and Ni3 Fe was comparatively studied. Two terminations of Ni3 Fe(211) were used to reveal the surface composition effect. The step of CH2 migration was proposed and incorporated into the mechanism. The termination with Fe locating at the step edge promotes methanation observably. The hydrogenation steps fit neatly a new Brønsted–Evans–Polanyi relationship.